Proceedings of the 18th International Conference on Hybrid Systems: Computation and Control 2015
DOI: 10.1145/2728606.2728629
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for hybrid cosimulation standards

Abstract: This paper defines a suite of requirements for future hybrid cosimulation standards, and specifically provides guidance for development of a hybrid cosimulation version of the Functional Mockup Interface (FMI). A cosimulation standard defines interfaces that enable diverse simulation tools to interoperate. Specifically, one tool defines a component that forms part of a simulation model in another tool. We focus on components with inputs and outputs that are functions of time, and specifically on mixtures of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 23 publications
(25 reference statements)
1
59
0
Order By: Relevance
“…Broman et al [8] give the model shown in Fig. 1 as a "simplest possible" nontrivial illustration of the challenges of hybrid co-simulation.…”
Section: A Motivating Examplementioning
confidence: 99%
See 4 more Smart Citations
“…Broman et al [8] give the model shown in Fig. 1 as a "simplest possible" nontrivial illustration of the challenges of hybrid co-simulation.…”
Section: A Motivating Examplementioning
confidence: 99%
“…For instance, the "getMaxStepSize" function of [7] is similar to the D ("deadline") function of [48]. Followup work includes [8], which proposes a collection of test cases together with acceptance criteria that can be used to determine whether a hybrid co-simulation technique is acceptable. Tripakis [47] investigates techniques to bridge the semantic gap between various formalisms (state machines, discrete-event models, dataflow, etc.)…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations